National Institute of Nursing Research Grant Funding Recipients: Hispanic and Nurses of Color Are Lagging. (September 2021) - Kippenbrock, Thomas; Emory, Jan
Introduction: National Institute of Health (NIH) stated in their strategic plan that a diverse research workforce is an important goal for the advancement of health care science; however, there is little evidence to show funding goes to National Institute of Nursing Research (NINR) minority nurse scientists. The study's aim was to determine NINR grant recipients' race/ethnicity, gender, and licensed nurse status. Methods: A descriptive research design was used with NIH providing NINR award recipients' names and employing organizations. An online survey with questions about their gender, race, ethnicity, and being a licensed nurse was sent to 619 award recipients. Results: Survey responses were collected from 135 NINR recipients receiving awards. Almost 50% NINR grant recipients were non-nurses. With licensed nurse recipients, White female was the dominate race and gender. Hispanic licensed nurses were 6.8% of the NINR grant recipients over the 3-year period. In addition, Asians and Blacks were the lowest race categories at 4.1% award percentage over the 3-year period. Conclusions: NIH strategic plan is for a diverse research workforce in order to advance health care science. NINR must lead the efforts to grow a diverse nursing workforce including Hispanic and underrepresented nurses in order to successfully compete in NINR grants and funding.